Communication between Husband and Wife in Negotiating a Parenting Role for their Child with Autism Spectrum Disorder (ASD) - Saptyasari, Andria (JURNAL KOMUNIKASI INDONESIA, 2020)
Families that have children with ASD (Autism Spectrum Disorder) were vulnerable in terms of financial, emotional, energy, and time that causes tension between husbands and wives as parents in caring for their children with ASD. The main purpose of this study is to elaborateon the communication used by married heterosexual couples in negotiating a parenting role related to financial, emotional, energy, and time problems for their child with ASD by using relational dialectical theory. The data collection method used interviews. The participants’ selection used snowball. The participants consisted of three married heterosexual couples with three different ages of children with ASD in East Java. The results showed that there are dynamic changes related to the role of married couple participants in meeting financial, emotional, time, and energy needs for their children with ASD who have difficulties in social communication and repetitive, restricted behavior. In meeting all those needs, each participant does role sharing change when necessary and share tasks with respect and responsibility.They also accommodate changes by using collective consensus. The conclusion of this study is a compromise strategy was used by them when sharing roles related to financial, emotional, time, and energy for children with ASD. Keluarga dengan anak ASD (Autism Spectrum Disorder) rentan akan kondisi finansial, emosional, tenaga dan waktu yang dapat memicu ketegangan antara suami dan istri sebagai orang tua dalam merawat anak ASD mereka. Studi ini bertujuanmengelaborasi komunikasi yang digunakan oleh pasangan heteroseksual yang sudah menikah dalam menegosiasikan peran merawat anak ASD terkait finansial, emosional, tenaga dan waktu dengan menggunakan teori dialektika hubungan. Metode pengumpulan data menggunakan wawancara. Cara mendapatkan tiga pasangan partisipan yang memiliki anak ASD dengan umur yang berbeda adalah dengan teknik snowball. Hasil menunjukkan ada perubahan yang dinamis terkait peran antar pasangan dalam memenuhi kebutuhan finansial, emosional, tenaga, dan waktu untuk anak ASD mereka yang memiliki kesulitan dalam komunikasi sosial. Setiap pasangan suami istri ini berusaha melakukan perubahan peran bila dibutuhkan dengan rasatanggung jawab dan saling menghargai satu sama lain. Mereka mengakomodasi perubahansecara kolektif dan melalui kesepakatan. Sehingga bisa disimpulkan dalam merawat anak ASD, mereka menggunakan strategi kompromi terkait finansial, emosional, tenaga, dan waktu.